Sociolinguistic Conditioning of Phonetic Category Realisation in Non-Native Speech - Waniek-Klimczak, Ewa (Research in Language, 2009)
The realisation of phonetic categories reflects a complex relationship between individual phonetic parameters and both linguistic and extra-linguistic conditioning of language usage. The present paper investigates the effect of selected socio-linguistic variables, such as the age, the amount of language use and cultural/social distance in English used by Polish immigrants to the U.S. Individual parameters used in the realisation of the category ‘voice’ have been found to vary in their sensitivity to extra-linguistic factors: while the production of target-like values of all parameters is related to the age, it is the closure duration that is most stable in the correspondence to the age and level of language proficiency. The VOT and vowel duration, on the other hand, prove to be more sensitive to the amount of language use and attitudinal factors.